Los procesos metodológicos inciden en la práctica del baloncesto de los estudiantes del primer segundo y tercer año de bachillerato de la unidad educativa fiscomisional Manuel José Rodríguez , de la parroquia Malacatos del cantón y provincia de Loja en el año lectivo 2012 -2013. Propuesta alternativa - Valdivieso Guaman, Darwin Armando (2014)
This research focuses on the study of the Methodological Processes affecting Physical Culture classes in basketball practice, students in first, second and third year of Bachelor of Education Unit Fiscomisional "José Manuel Rodríguez" the Malacatos parish. Posing as a central problem the study of methodological and technical education process and its impact on the practice of basketball as general objective raised to see how affects the methodological process of learning basketball as specific determine the incidence of planning teaching basketball and show that the teaching-learning process is suitable for the practice of the fundamentals of basketball. The literature review through a scientific theoretical foundation that helped me to know better the teaching of basketball. Using a methodologist and materials suitable for the development of research me facilitated obtaining results of the survey of a population of a teacher and a total of 100 high school students, per tucking the respective discussion of the results affirming or denying the hypotheses and thus be able to finish the respective conclusions and recommendations. All this has allowed me to develop an alternative methodology proposed the teaching of basketball fundamentals.